REPRESENTASI PEREMPUAN DALAM NOVEL MASYITOH KARYA AJIP ROSYIDI - Kurniadi, Dedi; Ristiani, Dian; Atmojo, Tekad Wadyo; Maurida, Lisa; Sariasih, Yanti (Universitas Muhammadiyah Palembang, 2023)
Novels as literary works always present various realities in society. One of the realities presented is the existence of quite complex gender relations and routines. This research aims to describe the representation of women in the novel Masyitoh by Ajip Rosidi. This study uses the theory of women's image which focuses on four aspects, namely physical aspects, psychological aspects, aspects in the family environment, and aspects in the community environment. The research was conducted using qualitative descriptive methods. Research data in the form of sentence quotations was collected using reading and note-taking techniques. Once collected, the data was processed and analyzed using interactive techniques. The research results show that the image of women in Masyitoh's novel is very complex and diverse. Judging from the physical aspect, women are imaged as beautiful and graceful. Viewed from a psychological aspect, the female antagonist is depicted as a rude figure, while the female protagonist is depicted as a woman who is worried, determined, brave and patient. Viewed from the family aspect, women are imaged as responsible, caring and loving, loyal and open figures. Meanwhile, if viewed from the perspective of their relationship with society, women are portrayed as humanist, humble and powerful.